A label-free cyclic assembly of G-quadruplex nanowires for cascade amplification detection of T4 polynucleotide kinase activity and inhibition1. Issue 17 (7th September 2015) - Shi, Zhilu; Zhang, Xiafei; Cheng, Rui; Li, Baoxin; Jin, Yan
<x xml:space="preserve">Abstract</x> A label-free and enzyme-free amplification strategy has been developed for sensitively and specifically studying PNK activity and inhibition via the hybridization chain reaction (HCR).